Development of the state audit system in Kazakhstan and the possibility of applying the experience - Uspambaeva, M.K.; Mandrazhi, Z.R.; Dauletova, R.S.; Kenbeilova, G.А.; Konakova, G.M. (KSU Publ., 2019)
The research shows the studies of the Kazakhstan state audit system on the example of the experience of the Republic of Latvia. The Latvian Republic is bound by the common membership in the European Union; the country preserves its individuality regarding the language, the culture and the history. And their common democracy is seen in different democratic systems and processes, as well as in distinct parliamentary, constitutional and administrative systems. It is against this backdrop that the supreme control body performs its activity in the Latvian Republic. The state audit in the Latvian Republic is more and more called «state control». The aim of the research is the understanding of the Latvian system for the state audit and the opportunities of its application in Kazakhstan, which may strengthen and lift the state audit to a quality level. The results allowed to offer a range of strategic directions in the development of the state audit system in Kazakhstan. The institution of the state audit exists nearly in all the countries in the world and has recently developed particularly dynamically. The state audit’s purpose is to control the budgetary funds and to assess legal use of the administrative resources in order to provide for a reasonable, economical and effective use of the funds. Normative and legal documents in the field of state audit of the countries are studied.
Қазақстанда мемлекеттік аудит жүйесін дамыту жəне жинақталған тəжірибені қолдану мүмкіндігі
Развитие системы государственного аудита в Казахстане и возможность применения опыта
Keywords: financial audit; budgetary funds; control; system; management; performance audit; state audit; statutory audit